Learedius learedi Price 1934 (Digenea, Spirorchiidae) in Chelonia mydas Linnaeus 1758 (Testudines, Chelonidae) in Brazil: case report - Werneck, M.R.; Becker, J.H.; Gallo, B.G.; Silva, R.J. [UNESP] (Universidade Federal de Minas Gerais (UFMG), Escola de Veterinária, 2006)
Relata-se a ocorrência de Learedius learedi Price 1934 (Digenea, Spirorchiidae) em Chelonia mydas Linnaeus 1758 (Testudines, Chelonidae) no Brasil. Onze animais foram examinados e destes, 54,6% estavam parasitados. Duzentos e cinqüenta e cinco exemplares de L. learedi foram recuperados de órgãos (coração, fígado, baço, pulmões, rins, mesentério) e do lavado corporal dos animais. Os resultados contribuem para o conhecimento da helmintofauna de quelônios marinhos e sua distribuição geográfica. Este é o primeiro registro da ocorrência de L. learedi na região do Atlântico Sul Ocidental.

This study reports the occurrence of Learedius learedi Price 1934 (Digenea, Spirorchiidae) in Chelonia mydas Linnaeus 1758 (Testudines, Chelonidae) in Brazil. Eleven animals were included in this study, 54.6 % of them were parasitized. Two hundred and fifty five parasite specimens were recovered from heart, liver, spleen, lungs, kidneys, mesenterium, and body wash. Results contribute to the knowledge about the helminthofauna of marine chelonian and their geographical distribution. This is the first report of L. learedi in the Southwestern Atlantic.
Learedius learedi Price 1934 (Digenea, Spirorchiidae) em Chelonia mydas Linnaeus 1758 (Testudines, Chelonidae) no Brasil: relato de caso
Keywords: Learedius learedi; Chelonia mydas; Spirorchiidae; Chelonidae; novo hospedeiro; Learedius learedi; Spirorchiidae; Chelonia mydas; Chelonidae; new host